Comparison of Cervical Kinematics, Pain, and Functional Disability Between Single- and Two-level Anterior Cervical Discectomy and Fusion. Issue 15 (1st August 2016) - Chien, Andy; Lai, Dar-Ming; Wang, Shwu-Fen; Hsu, Wei-Li; Cheng, Chih-Hsiu; Wang, Jaw-Lin
Abstract : Study Design: A prospective, time series design. Objective: The purpose of this study is two-fold: firstly, to investigate the impact of altered cervical alignment and range of motion (ROM) on patients' self-reported outcomes after anterior cervical discectomy and fusion (ACDF), and secondly, to comparatively differentiate the influence of single- and two-level ACDF on the cervical ROM and adjacent segmental kinematics up to 12-month postoperatively. Summary of Background Data: ACDF is one of the most commonly employed surgical interventions to treat degenerative disc disease. However, there are limited in vivo data on the impact of ACDF on the cervical kinematics and its association with patient-reported clinical outcomes. Methods: Sixty-two patients (36 males; 55.63 ± 11.6 yrs) undergoing either a single- or consecutive two-level ACDF were recruited. The clinical outcomes were assessed with the Pain Visual Analogue Scale (VAS) and the Neck Disability Index (NDI). Radiological results included cervical lordosis, global C2-C7 ROM, ROM of the Functional Spinal Unit (FSU), and its adjacent segments. The outcome measures were collected preoperatively and then at 3, 6, and 12-month postoperatively. Results: A significant reduction of both VAS and NDI was found for both groups from the preoperative to 3-month period ( P  < 0.01). Pearson correlation revealed no significant correlation between global ROM with neither VAS ( P  = 0.667) nor NDI ( P  = 0.531). A significant reduction of global ROM was identified for the two-level ACDF group at 12 months ( P  = 0.017) but not for the single-level group. A significant interaction effect was identified for the upper adjacent segment ROM ( P  = 0.024) but not at the lower adjacent segment. Conclusion: Current study utilized dynamic radiographs to comparatively evaluate the biomechanical impact of single- and two-level ACDF. The results highlighted that the two-level group demonstrated a greater reduction of global ROM coupled with an increased upper adjacent segmental compensatory motions that is independent of patient-perceived recovery. Level of Evidence: 3